Does clinical training improve mentalization skills in future therapists? A comparison of first and last year students of clinical psychology and of engineering - Fagerbakk, Steffen André; Sørhøy, Silje Helen; Nilsen, Torbjørn; Laugen, Nina Jakhelln (Frontiers in Psychology, 2023)
Objective: Mentalization has been suggested as a therapist skill that might be important for therapeutic success. The aim of this study was to explore whether the mentalization capacity of students of clinical psychology differs from other students, and whether last-year students differ from first-year students. Method: A total of 297 students participated in this study, recruited from first and last years of psychology and engineering study programs. All participants filled out the MentS, a self-report measure of mentalization capacity. Results: No significant differences were found in self-reported mentalization capacity between first and last year students of clinical psychology. The results did however show that first year students of psychology had significantly higher self-reported mentalization skills compared to students of engineering, and higher MentS-scores were associated with gender (female) and higher age. Conclusion: The finding that students of clinical psychology rate themselves as having a higher capacity to mentalize compared to students of engineering might suggest that individuals with a higher capacity to mentalize are more likely to engage in clinical psychology and become therapists. However, the lack of significant difference in self-reported mentalization capacity in last year students of clinical psychology compared to first year students might indicate that the Norwegian education in clinical psychology does not succeed in enhancing mentalization in future therapists. Clinical psychology study programs might benefit from targeted mentalization training.